Karakter Bangsa dan Tantangan Bela Negara di Era Google Veo 3 dalam Perspektif Damai dan Resolusi Konflik - Junior Ternama Siahaan; Halomoan FS Alexandra; Parluhutan Sagala (Pendekar: Jurnal Pendidikan Berkarakter, 2025)
Abstract: The advancement of generative visual technology, particularly Google Veo 3, has significant implications for national character and the challenges of national defense in the digital era. This technology enables the creation of realistic videos from simple text, which, on one hand, can be utilized for educational purposes, but on the other hand, opens opportunities for the dissemination of visual disinformation such as deepfakes. This study adopts a descriptive-analytical focus, employing a literature review with a thematic content analysis approach on relevant literature and case studies regarding the use of Google Veo 3, to examine its impact on social stability, democratic processes, and the values of Pancasila from the perspective of Peace and Conflict Resolution. The analysis reveals that this technology has the potential to serve as an instrument of conflict through the manipulation of public perception, identity politics, and the delegitimization of state institutions. However, other findings indicate that these risks can be mitigated through digital literacy, the strengthening of national ethics, and cross-sector collaboration. This study emphasizes that national defense in the digital era encompasses not only physical protection but also cognitive and ideological efforts to safeguard national identity amidst the escalating visual information warfare.Abstrak: Kemajuan teknologi generatif visual, khususnya Google Veo 3, memiliki implikasi signifikan terhadap karakter bangsa dan tantangan bela negara di era digital. Teknologi ini memungkinkan pembuatan video realistis dari teks sederhana, yang di satu sisi dapat dimanfaatkan untuk edukasi, namun di sisi lain membuka peluang penyebaran disinformasi visual seperti deepfake. Penelitian ini berfokus pada deskriptif analitik yang menggunakan studi Pustaka dengan pendekatan analisis isi tematik (thematic content analysis) terhadap literatur dan studi kasus terkait pemanfaatan Google Veo 3, untuk menelaah dampaknya terhadap stabilitas sosial, proses demokrasi, dan nilai-nilai Pancasila dalam perspektif Damai dan Resolusi Konflik. Hasil analisis menunjukkan bahwa teknologi ini berpotensi menjadi instrumen konflik melalui manipulasi persepsi publik, politik identitas, dan delegitimasi institusi negara. Namun, temuan lain mengindikasikan bahwa risiko tersebut dapat ditekan melalui literasi digital, penguatan etika kebangsaan, dan kerja sama lintas sektor. Studi ini menegaskan bahwa bela negara di era digital tidak hanya mencakup pertahanan fisik, tetapi juga perjuangan kognitif dan ideologis dalam melindungi identitas nasional di tengah eskalasi perang informasi visual.